Inibição sistêmica da NADPH oxidase: estudo do coração de ratos espontaneamente hipertensos com diabetes mellitus - Bassetto, Camila Moreno Rosa [UNESP] (2015)
Cardiovascular diseases (CVD) are the major cause of morbidity and mortality worldwide. Diabetes mellitus (DM) and arterial hypertension (AH) are the main risk factors for the development of CVD. The coexistence of diabetes and hypertension is common and leads to an increased risk of cardiovascular events. Organs damage caused by hypertension and DM have been associated with increased oxidative stress. Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase enzymes family is a major source of reactive oxygen species in the cardiovascular system. Apocynin (APO) has been characterized as an inhibitor of NADPH oxidase since the 1980's decade. Despite promising evidence of APO in the treatment of many diseases, there are studies questioning its power as an inhibitor of NADPH oxidase. Besides controversies on the use of apocynin in blocking NADPH oxidase in non-phagocytic cells, few studies have evaluated the effects of its blockade on cardiac remodeling. In addition, there is a lack of information when AH and DM are associated. Therefore, the aim was to analyze the influence of NADPH oxidase inhibition by apocynin on cardiac remodeling in spontaneously hypertensive rats (SHR) with diabetes mellitus. Methods: Seven-month-old male SHR were divided into four groups: control (CTL, n=18); CTL+APO (n=18); DM (n=20); DM+APO (n=20). DM was induced by streptozotocin (40 mg/kg, i.p., single dose). CTL+APO and DM+APO groups received APO (16 mg/kg/day, diluted in the water) for 8 weeks. In vivo cardiac structures and functions were assessed by echocardiogram. In vitro functional study was performed by left ventricular papillary muscle study. In vitro left ventricle (LV), right ventricle and atria weights were measured. Samples of these structures, liver and lung were used to calculate the wet/dry weight ratio. LV tissue samples were obtained to measure myocyte diameters, interstitial collagen fraction, and hydroxyproline concentration. Left ...